2cos^2(x)+5/4(sin^2(2x))-sin^2(x)+cos2x=0

2cos^2(x)+5/4(sin^2(2x))-sin^2(x)+cos2x=0
Гость
Ответ(ы) на вопрос:
Гость
2cos²x+5/4*sin²2x-sin²x+cos²x-sin²x=0 3cos²x+5/4*sin²2x-2sin²x=0 3(1+cos2x)/2+5/8(1-cos4x)-(1-cos2x)=0 12+12cos2x+5-5cos4x-8+8cos2x=0 -10cos²x+5+20cos2x+9=0 cos2x=a 5a²-10a-7=0 D=100+140=240 a1=(10-4√15)/10=1-0,4√15⇒cos2x=1-0,4√15⇒ 2x=+-arccos(1-0,8√15)+2πn⇒x=+-0,5arccos(1-0,8√15)+πn,n∈z a2=(10+4√15)/10=1+0,4√15⇒cos2x=1+0,4√15>1 нетрешения
Не нашли ответ?
Ответить на вопрос
Похожие вопросы